Acoustic field-assisted inkjet-based additive manufacturing of carbon fiber-reinforced polydimethylsiloxane composites. (August 2022) - Liu, Chang; Pandit, Partha Pratim; Parsons, Cole; Khan, Fazeel; Hu, Yingbin
Abstract: Owing to its high biocompatibility, good chemical and thermal stability, and outstanding optical properties, polydimethylsiloxane (PDMS) has received broad acceptance in the production of biomedical, electrical, wearable equipment, and other high-tech industries. However, the poor mechanical properties of PDMS limit its use to low stress applications. To overcome this shortcoming, milled carbon fiber (CF) was added to create CF-reinforced PDMS composites using an inkjet-based additive manufacturing (AM) technology. To reduce internal defects such as voids and to achieve a homogeneous CF distribution in the CF-reinforced PDMS composites, an acoustic field (AF) was introduced to the inkjet-based AM technology. Experimental results show that the application of the AF is beneficial for reducing defects and homogenizing CF distribution in fabricated samples. In addition, the samples processed with the AF demonstrate improved tensile properties, notably percentage elongation and toughness and enhanced dynamic mechanical properties (such as storage modulus) when compared to non-AF samples. Highlights: An inkjet additive manufacturing technology was integrated with an acoustic field. Effects of the acoustic field on microstructure characterizations were studied. Effects of the acoustic field on mechanical properties were studied. Voids removal and reinforcement dispersion mechanisms were investigated.